Restrictive mitral annuloplasty with or without coronary artery bypass grafting in ischemic mitral regurgitation. (13th May 2020) - Kainuma, Satoshi; Toda, Koichi; Miyagawa, Shigeru; Yoshikawa, Yasushi; Hata, Hiroki; Yoshioka, Daisuke; Kawamura, Takuji; Kawamura, Ai; Ueno, Takayoshi; Kuratani, Toru; Kondoh, Haruhiko; Masai, Takafumi; et al.
Abstract: Aims: In patients with ischaemic mitral regurgitation (MR), the impact of mitral valve surgery with concomitant coronary artery bypass grafting (CABG) on post‐operative survival and left ventricular (LV) reverse remodelling remains unknown. Therefore, we investigated these outcomes following restrictive mitral annuloplasty (RMA) with and without CABG in those patients. Methods and results: This study included 309 patients with chronic MR and ischaemic cardiomyopathy for whom concomitant CABG was indicated ( n = 225) or not indicated ( n = 84) with RMA. The primary endpoint was all cause mortality during the follow‐up, and the secondary endpoint was defined as the composite of mortality and re‐admission for heart failure. Linear mixed model was used to analyse serial echocardiographic changes in LV function. To reduce the impact of treatment bias and potential confounding in the direct comparisons between patients who underwent RMA with and those who underwent it without CABG, we established weighted Cox proportional‐hazards regression models with inverse‐probability‐of‐treatment weighting. Pre‐operatively, there were no intergroup differences in age (RMA with CABG, 67 ± 9 vs. RMA without CABG, 68 ± 11, P = 0.409) and logistic EuroSCORE II (16 ± 14 vs. 15 ± 15%, P = 0.496). The 30‐day mortalities were 2.7% and 3.6%, respectively ( P = 0.67). During follow‐up with a mean duration of 72 ± 37 months (range, 5.6–179), there were 157 deaths and 105 re‐admissions for heart failure. Overall 1‐year and 5‐year survival rates were 83 ± 2% and 58 ± 3%, respectively. Patients who did not receive CABG with RMA had a significantly lower 5‐year survival rate (45% vs. 63%, P = 0.049) and freedom from adverse events defined as mortality and/or admission for heart failure (19% vs. 43%, P < 0.001) than those who did. After adjustments for clinical covariates with inverse‐probability‐of‐treatment weighting, concomitant CABG was identified as an independent protective factor for adverse events (hazard ratio: 0.53; 95% confidence interval: 0.44–0.64; P < 0.001). Along with significant MR reduction, LV function parameters changed over time after surgery in both groups, with greater improvements in patients who underwent RMA with CABG (time effect, P < 0.001; and interaction effect, P = 0.002). Conclusions: RMA can be performed with an acceptable operative mortality, irrespective of indications for CABG. Patients with ischaemic MR for whom CABG is indicated with RMA are more likely to show better long‐term and event‐free survival and greater improvements in LV systolic function. The optimal revascularization strategy should be discussed with a heart team whenever indicated in patients with ischaemic MR; otherwise, they may miss the opportunity to benefit from concomitant CABG during subsequent RMA.